Implementation Of Duties, Functions And Authority Of The Integrated Law Enforcement Center (Gakkumdu) In Realizing Democratic, Integrity And Fair Elections And Elections (Study In Pematangsiantar City) - Daulat Nathanael Banjarnahor; Sepriandison Saragih; Firinta Togatorop; Michael F Sihombing (LPPM Universitas PGRI Sumatera Barat, 2024)
General elections as a means of realizing people's sovereignty in Indonesia are one of the essences of the Constitution of the Republic of Indonesia, the 1945 Constitution (UUD 1945). The aim of conducting this research is so that every time post-conflict elections and local elections are held, evaluations carried out by election experts and activists can explain the problem of weak election law enforcement. The problem of weak election enforcement stems from the many administrative violations and criminal election law violations that have not been completely resolved. The research method used to answer the problems in this scientific paper is the Normative-Empirical Legal Research Method (Applied Legal Research), with the nature of prescriptive research. This method uses normative-empirical legal case studies in the form of legal behavioral products. Based on the research results, there are weaknesses in the implementation of elections and regional elections in Indonesia. The government takes lessons learned and then makes improvements so that the implementation of elections and regional elections can be better. One form of monitoring the implementation of elections and regional elections is the establishment of the Gakkumdu (Integrated Law Enforcement) Hall. Conclusion that can be drawn: The Gakkumdu Center is a mandate from Law no. 7 of 2017 concerning General Elections. Example: Article 486 paragraph 1 states that in order to equalize understanding regarding the handling of election crime cases, Bawaslu, the Police and the Prosecutor's Office formed Gakkumdu to handle election crime cases, so that they are fair, transparent and free from irregularities and have interests. authority as stated in the Regulations. Bawaslu Number 3 of 2023